The Role of Rituals in the Structure of Traditional City (The Case Study: Shushtar City) - Mohammad Ebrahim Mazhary; Fatemeh Poodat (توسعه اجتماعی)
Over the centuries, religious symbols and rituals have dictated the specific order to the structure of traditional cities, the reason by which, many cities in the past were able to respond to psychological needs of the residents. The rituals that are performed during the years, affect the structure of the city without which analyzing the form and structure of the city is not possible. This research aims to study the effect of rituals on the structure of traditional cities and Shushtar is chosen as the case study. This research investigates the role of rituals in particular the ceremony of Moharam in enhancing the disturbances resulted from modification of historical structure of the city and its spatial order. This research shows that the rituals break the modern structure of the city into the integrated stage area. “Takiya”s, shrines, “Hoseinia”s and mosques as religious and ceremonial places are focal points within the city structure. During ceremonies, the city abandons its daily routine and transforms in to an integrated stage for a great Theater. This Theater, performed by the citizens, reveals the connectivity between residents and city more than ever. Furthermore the focal religious points play a critical role in the ritual ceremonies. Therefore the morphology of the city needs to adjust to the ceremony to become connected and homogeneous. In that adjustment, modern urban elements, that fragmented the city structure, applied as an effective element during the ceremonies.